Insights into Collaborative Economy Research in Ibero-America: A Systematic Review of the Scientific Literature Available in Spanish in Scopus - Gago-Chávez, Johanna de Jesús Stephanie; Wong-Cabanillas, Francisco Javier; Soria-Cuellar, Fidel Tadeo; Vega-Vidal, Carlos Alberto; Suyo-Vega, Josefina Amanda; Meneses-La-Riva, Monica Elisa; Fernández-Bedoya, Víctor Hugo (LACCEI, 2024)
Collaborative economy, a novel economic model, accesses resources and benefits via shared services, omitting ownership. It’s categorized into 5 groups: sharing physical goods, skills, funding, knowledge, and consumption. This study aimed to address the following research questions: a) What are the research papers on collaborative economy in Ibero-America, published in Spanish, available on the Scopus database? b) From which countries do the research papers on collaborative economy in Ibero-America, published in Spanish, originate in the Scopus database? c) What sector do they belong to, and what type of collaborative economy is detailed in the research papers on collaborative economy in Ibero-America, published in Spanish, available on the Scopus database? d) What are the main findings described in the research papers on collaborative economy in Ibero-America, published in Spanish, available on the Scopus database? To address these research questions, a systematic review was conducted on the Scopus database. The initial search for "collaborative economy" yielded 41 initial investigations, from which, after applying 7 exclusion criteria filters (temporality, full access, original article, country of origin, language, duplicity, and relevance), the final identification of 10 scientific articles was achieved. As for the conclusions, the study of collaborative economy reveals innovative business models that challenge existing regulations and policies. It affects labor dynamics, market competition, fosters innovation, and enhances social cohesion. Additionally, by promoting shared resource usage, it contributes to environmental sustainability, playing a crucial role in understanding modern society’s complexity